2009
DOI: 10.3109/00016480903311880
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergic rhinitis among the adult population in Turkey

Abstract: A total of 4125 volunteers participated in the study; 2200 were female and 1925 were male. On the basis of self-reporting, 23.1% of the study population was considered to have AR (males 22.3%, females 23.8%). On the other hand, the prevalence of physician-diagnosed AR was 20.1% (males 19.7%, females 20.4%). The prevalence of self-reported AR was 23.8% in the urban and 18.4% in the rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 17 publications
2
19
0
7
Order By: Relevance
“…A high prevalence of allergies in urban (compared to rural) areas was reported in Germany, Poland, and Turkey [24-26]. Our inner cities have unique living conditions including high humidity, use of air conditioning, frequent house molds and traffic pollution.…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of allergies in urban (compared to rural) areas was reported in Germany, Poland, and Turkey [24-26]. Our inner cities have unique living conditions including high humidity, use of air conditioning, frequent house molds and traffic pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, studies have indicated wide variations in prevalence of AR or AR/C between the countries, as well as within different regions of individual countries (Fig. and Table ) . These range from 2.9% AR and 3.8% AR/C in children from one region in Turkey to 54.1% AR and 39.2% AR/C in 13–14‐year‐old children in one region in Nigeria .…”
Section: Prevalence Of Ar or Ar/cmentioning
confidence: 97%
“…The prevalence of AR or AR/C has been investigated in a large number of studies conducted in different regions of the country , with the majority investigating prevalence of disease in children using the standardized ISAAC study . Studies employing the ISAAC study protocol have indicated the prevalence of AR in children aged 6–18 years to range from 2.9% in Sanliurfa, a socio‐economically deprived city with high rates of infectious and parasitic diseases and hot dry climate, in south‐eastern Turkey to 37.7% in Zonguldak, a highly industrialized city with high usage of unrefined coal without domestic or industrial air‐filtrating systems, in north‐west Turkey .…”
Section: Prevalence Of Ar or Ar/cmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study regarding the prevalence of allergic rhinitis in Turkey [10], many volunteers offered information about HTs that they had used to treat their allergic rhinitis symptoms. Here, we examine the use of HTs by patients with allergic rhinitis in Eskişehir, Turkey.…”
Section: Introductionmentioning
confidence: 99%